[PP.25.10] BODY MASS INDEX AND CONTRALATERAL RATIO PREDICT BLOOD PRESSURE OUTCOME FOLLOWING UNILATERAL ADRENALECTOMY IN PRIMARY ALDOSTERONISM. (September 2016) - Bokuda, K.; Ichihara, A.; Yatabe, M.; Yatabe, J.; Ando, T.; Morimoto, S.
Abstract : Objective: Effect of unilateral adrenalectomy on blood pressure (BP) outcome in primary aldosteronism (PA) is diverse. It has also been reported that medication with mineralocorticoid receptor blocker has equivalent effect to that of surgical treatment, making it difficult to select appropriate treatment. Therefore, we sought to investigate preoperative factors contributing to postoperative BP outcome, retrospectively. Design and method: Data on 96 PA patients who underwent unilateral adrenalectomy at our institution, from January 2000 to February 2015 were collected and categorized to cured (<140/90 mmHg with no antihypertensive drug) and not cured group (with any antihypertensive drugs), based on postoperative BP. Patient demographics, blood and urine samples, tumor size, loading tests (captopril loading test, furosemide upright test and saline loading test) and adrenal vein sampling (AVS) were evaluated. Results: 46 patients were categorized as cured and 50 patients were categorized as not cured. There were significantly more males in not cured group. Age at surgery (47 ± 12 vs. 55 ± 10, p = 0.0009), body mass index (BMI) (21.8 ± 3.4 vs. 24.6 ± 3.0, p = < .0001), number of antihypertensive drugs prescribed (1.1 ± 0.7 vs. 1.5 ± 1.0, p = 0.0338) and uric acid (UA) (4.4 ± 1.1 vs. 5.5 ± 1.4, p = <.0001) were significantly higher in not cured group. There were no differences in tumor size or the results of loading tests between the two groups. Contralateral ratio (CR) after adrenocorticotropic hormone stimulation was significantly lower (0.4 ± 0.2 vs. 0.7 ± 0.6, p = 0.0003) in cured group. There were no differences in other parameters. In the multivariate model, BMI (p = 0.0473) and CR (p = 0.0199) significantly correlated with resolution outcome, however gender, age, numbers of antihypertensive medications and UA did not. The optimum cutoff value of BMI was 23.2 (sensitivity, 67.4 %; specificity, 74.0 %) and 0.5 for CR (sensitivity, 82.9 %; specificity 42.9 %). Conclusions: BMI and CR significantly correlated with BP outcome after adrenalectomy. Referring to BMI and CR preoperatively may be helpful to select appropriate treatment for PA patients.